Pemanfaatan Media Sosial sebagai Sistem Informasi Dakwah dalam Meningkatkan Partisipasi Generasi Z pada Akun TikTok Kadam Sidik - Hilda Rahmadani Harahap; Afridal Hazaqi Tambunan; Daratul Laila (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
The digital era has transformed Islamic da'wah from conventional methods into more interactive and accessible forms through social media platforms such as TikTok. This research aims to analyze the utilization of social media as a da'wah information system in increasing Generation Z participation on Kadam Sidik's TikTok account (@basyasman). Using a qualitative descriptive method, data were collected through systematic observation, documentation, and analysis of audience interactions within the platform. The findings reveal that Kadam Sidik successfully attracts and maintains audience engagement by prioritizing logical, contextual, and substantial Islamic studies that are closely related to contemporary youth issues without relying on viral music trends or sensational content. Furthermore, the communication strategy employed, characterized by a casual, persuasive, and interactive approach through comment sections and live streaming features, effectively encourages active participation in the form of likes, comments, shares, and discussions. The study highlights that adaptive content presentation, credibility of the da'i, and audience-oriented communication are essential factors in ensuring the sustainability of digital da'wah. It concludes that an integrated information system on TikTok can transform the platform into a credible and effective medium for religious education among the digital generation.